Charge storage and transport mechanisms in printable supercapacitors - Wee, Grace Tsyh Ying (2011)
Supercapacitors (SCs) exhibiting 20 to 200 times greater capacitance and energy density (5 Wh kg-1, 80-100 F g-1) than conventional capacitors and delivering higher power density ( 10 kW kg-1) than batteries, represent an unique class of technology with niche applications amongst other energy storage devices. While conventional SCs suffer from its bulky architecture comprising of metallic current collectors and amorphous carbon, incorporation of the carbon nanotubes (CNTs) network as a single-layer current collector and active material has been explored, which leads to a light-weight and printable charge storage device that offers a “printed power solution” that can be potentially integrated with printed electronics applications.